Depression, self-esteem and narcissism and its association with Facebook use - Tisaker, Nurain (Department of Psychology, 2017)
Based on extensive research from the USA, Europe and Asia into mental health symptoms, it has been suggested that mental health might be influenced by social networking use, and specifically Facebook. It is evident that there is a gap in studies and local research into mental health and social networking. From a South African perspective, there appears to be no known research conducted in this field, and therefore the rationale for the present study was based on the observation that, as a large proportion of South African internet users also use Facebook, it would be fruitful to focus on whether mental health symptoms were influenced by Facebook use in a South African setting. The study adopted a quantitative approach to explore different hypotheses. The hypotheses included whether more Facebook activity might correlate with an increase in feelings of depression (Hypothesis 1); whether there was a correlation between individuals with low self-esteem and their level of Facebook activity (Hypothesis 2); and whether high narcissism scores in individuals indicated a correlation with increased or high levels of Facebook activity (Hypothesis 3). A total of 336 participants who were students from the University of Cape Town (UCT) completed the survey, which comprised several questionnaires. The first questionnaire required participants to provide their demographic information. The second measure addressed their Facebook online activity, requiring that participants indicate how many times they check their Facebook page each day, the time spent on Facebook per session, and how they accessed Facebook. Other questionnaires assessed the psychological constructs of depression, self-esteem and narcissism, using existing scales. These included the Beck Depression Inventory (BDI-II); the Centre for Epidemiologic Studies Depression Scale (CES-D); the Rosenberg Self-esteem Scale (RSES); and the Narcissism Personality Inventory (NPI-16). The data were analysed across several steps, including descriptive statistics, to explore demographics (i.e. age, sex and race); then participants' scores on the psychological constructs (BDI-II, CES-D, RSES, and NPI-16) were explored to gain an overall impression of the sample and a basic understanding of how participants scored on the various psychological constructs. Thereafter Pearson correlations were calculated to assess whether participants' scores on the psychological constructs correlated with their Facebook activity, as measured by their time spent, the number of times they checked Facebook, and their method of access. The results indicated that there was no significant relationship between Facebook activity and the psychological constructs explored. This finding contradicts various studies discussed in the literature review, some of which suggest that Facebook use could have a negative effect on depressive symptoms, self-esteem and narcissistic traits, and some which suggest that Facebook use could have a positive effect on mental health.